Transbronchial cryobiopsy using the ultrathin 1.1-mm cryoprobe with ultrathin bronchoscopy under radial endobronchial ultrasound guidance for diagnosis of peripheral pulmonary lesions - Hasselbring, Franziska; Herth, Felix; Kriegsmann, Mark; Kriegsmann, Katharina; Eberhardt, Ralf (Respiration, 2024)
Introduction: Today, the increasing number of incidentally detected peripheral pulmonary lesions (PPLs) within and outside lung cancer screening trials is a diagnostic challenge. This fact encourages further improvement of diagnostic procedures to increase the diagnostic yield of transbronchial biopsy, which has been shown to have a low complication rate. The purpose of this study was to evaluate the safety and feasibility of a new ultrathin 1.1 cryoprobe that can be placed through an ultrathin bronchoscope (UTB) using fluoroscopy and radial endobronchial ultrasonography (rEBUS) navigation for assessing PPLs. Methods: Thirty-five patients with PPL less than 4 cm in diameter were prospectively enrolled to receive transbronchial cryobiopsies (TBCBs) using the ultrathin 1.1-mm cryoprobe. Navigation to the PPL was accomplished with the UTB. Under rEBUS and fluoroscopy guidance up to 4 cryobiopsies were obtained. The sample sizes of the biopsies were compared to a historic collective derived from a 1.9-mm cryoprobe and standard forceps. The feasibility and safety of the procedure, the cumulative and overall diagnostic yield, and the cryobiopsy sizes were evaluated. Results: After detection with the rEBUS, TBCB was collected from 35 PPLs, establishing a diagnosis in 25 cases, corresponding to an overall diagnostic yield of 71.4%. There was no difference in diagnostic yield for PPL <20 mm or ≥20 mm. All cryobiopsies were representative with a mean tissue area of 11.9 ± 4.3 mm2, which was significantly larger compared to the historic collective (p = 0.003). Six mild and four moderate bleeding events and 1 case of pneumothorax were observed. Conclusions: Using the ultrathin 1.1-mm cryoprobe combined with an UTB for rEBUS-guided TBCB of PPL is feasible and safe. This diagnostic approach improves bronchoscopic techniques for diagnosing peripheral lung lesions and may contribute to improve diagnosis of lung cancer even in small PPL.